Estudio de la señalización horizontal del centro histórico de la ciudad de Riobamba como una propuesta de un plan alternativo de recorrido mediante ubicación de la señalización en el periodo 2014 – 2015 - Villa Uvidia, Mario Mauricio (2016)
This research was developed under the guidelines, regulations and existing processing work degree at the National University of Chimborazo standards. This work is a technical study of signaling in the historic center of the city of Riobamba, which aims to identify the state, the percentage of existence and efficiency for the mobility of those who circulate in this area of ​​study. Whereupon an alternative mitigation and improved mobility based on national and international technical standards for horizontal signage sector proposed. To do this research has been divided into the following chapters: Chapter 1 provides the reference framework that will allow us to demonstrate similar work done at national, Latin American level and have succeeded in improving mobility. Chapter 2, will allow us to conceptualize the parameters and guidelines established for the development of research. Chapter 3, allows use suitable for the analysis of the existence of a problem in the horizontal signage in the historic center of the city of Riobamba methodologies. Chapter 4 focuses on the verification of the methodologies used for the implementation of the road marking the historic center of the city of Riobamba. Chapter 5 presents the conclusions and recommendations of the investigated problem and consequently propose an alternative plan to improve mobility in the study area.